Dialogue skill of educational counselors (Journal of the College of Basic Education, 2022)
The research aimed to identify: the dialogue skill of educational counselors, and the significance of the difference in the dialogue skill of educational counselors according to the gender variable (males)./ females), marital status (married / unmarried), length of service (1 - 5 years/6 years and above) and in order to achieve the objectives of the research, the researchers relied on the dialogue skill scale which they prepared according to Thorne’s theory, and the scale consisted of (21) positionsverballyIts characteristics were confirmed, as the scale was applied to a sample of (200) male and female guides, who were chosen in a cluster random manner, and the results of the research showed that the individuals of the research sample possess the skill of dialogue according to the hypothetical mean, there are no statistically significant differences in the skill of dialogue according to the variable of gender and social status. and duration of service. In light of the results, the researchers presented a number of recommendations and suggestions.